Penatalaksanaan Fisioterapi Pada Kasus Fracture Tibia Plateau Dextra Di RSUD Sragen - ANGGRAINI, Fenti Siska, Arif Pristianto, SSt.FT.,M.Fis (2014)
Background : Fracture Tibia Plateau is due to compression fractures of the tibia on the femur top, causing damage to one side. Tibial plateau fracture occurs because the lateral femoral condylus impelled towards the tibia, and the cruciate ligaments and medial often torn. Aim Of Research : To investigate the implementation of physiotherapy in reducing pain, increasing range of motion, and improving muscle strength in patients Tibia Plateau Fracture Dextra using exercise therapy modalities. Results : After therapy for about six times the obtained results of the assessment of pain in motion pain T1: 6 to T6: 4, tenderness T1: 5 to T6: 3, silent pain T1: 1 to T6: 1. Increased range of motion of hip S: T1: 0°- 0°- 80° be T6: 0°-0°-110°, F: T1: 0°-0°-15° be T6: 0°-0°-25°, LGS Knee S: T1: 0°-0°-0° be T6: 0°-40°-5°, LGS Ankle S: T1: 0°-10°-10° be T6: 0°-20°-20°. Increased muscle strength flexion, extension, abduction, adduction Hip at T1: 3 become T6: 4, flexion, extension Knee on T1: 3 become T6: 4, flexion, extension Ankle T1: 3 be 4 Conclusion : Exercise therapy can reduce pain, improve LGS, increase muscle strength.